2020
DOI: 10.3390/pathogens9090688
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course and Gross Pathological Findings in Wild Boar Infected with a Highly Virulent Strain of African Swine Fever Virus Genotype II

Abstract: African swine fever (ASF) is a notifiable disease that in recent years has spread remarkably in Europe and Asia. Eurasian wild boar (Sus scrofa) plays a key role in the maintenance and spread of the pathogen. Here we examined gross pathology of infection in wild boar with a highly virulent, hemadsorbing genotype II ASF virus (ASFV) strain. To this end, six wild boars were intramuscularly inoculated with the 10 HAD50 Arm07 ASFV strain, and 11 wild boars were allowed to come into direct contact with the inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 29 publications
5
26
1
1
Order By: Relevance
“…The combination of a strong humoral response and high levels of IFN-γ might have protected the vaccinated animals from the virulent isolate. These results coincide with those of previous studies, in which elevated IFN-γ levels have been associated with specific immune responses [14,47,48]. For instance, it has been reported that the deletion of IFN-γ inhibitor genes DP148R, MGF360, and 530/505 genes from ASFV Benin97/1 isolate induced protective immune responses against a challenge [35], thus showing the importance of this cytokine in regards to triggering an effective immune response against the virus.…”
Section: Discussionsupporting
confidence: 91%
“…The combination of a strong humoral response and high levels of IFN-γ might have protected the vaccinated animals from the virulent isolate. These results coincide with those of previous studies, in which elevated IFN-γ levels have been associated with specific immune responses [14,47,48]. For instance, it has been reported that the deletion of IFN-γ inhibitor genes DP148R, MGF360, and 530/505 genes from ASFV Benin97/1 isolate induced protective immune responses against a challenge [35], thus showing the importance of this cytokine in regards to triggering an effective immune response against the virus.…”
Section: Discussionsupporting
confidence: 91%
“…Some animals had slight erythema, ocular and nasal discharges, slight walking difficulties, and an increased respiratory rate. These observations were previously detailed by Rodríguez-Bertos et al [ 22 ].…”
Section: Resultssupporting
confidence: 58%
“…Because of the lack of differences with regard to clinical course, pathological findings, and virus presence in tissues ( Supplementary Table S1 ) between the intramuscularly inoculated or in-contact animals, we considered the six wild boars intramuscularly inoculated and the 11 in-contact wild boars in a single group, denominated as the virulent group. Their study period lasted 15 days, as described previously by Rodríguez-Bertos et al [ 22 ] ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations